An introduction to social marketing - McAuley, Andrew; Rundle-Thiele, Sharyn (Henry Stewart Talks, 2012)
The effectiveness of marketing, Commercial origins, Defining social marketing, social marketing in practice, Examples from obesity, Children's snacking habits, Alcohol and car crashes, creating social change, Individual level change, Community level change, Principles for social change